#### Answer

$-9z+27$

#### Work Step by Step

The distributive property holds that $a(b+c)=ab+ac$ for real numbers a, b, and c.
Therefore, $-9(z-3)=-9(z)+(-9(-3))=(-9\times z)+(-9\times-3)=-9z+27$.

Published by
Pearson

ISBN 10:
0134467795

ISBN 13:
978-0-13446-779-5

$-9z+27$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.